Beta amyloid protein deposition in the brain after severe head injury: implications for the pathogenesis of Alzheimer's disease. Issue 4 (April 1994) - Roberts, G W; Gentleman, S M; Lynch, A; Murray, L; Landon, M; Graham, D I
Abstract : In a recent preliminary study it was reported that a severe head injury resulted in the deposition of beta amyloid protein (beta AP) in the cortical ribbon of 30% of patients who survived for less than two weeks. Multiple cortical areas have now been examined from 152 patients (age range 8 weeks-81 years) after a severe head injury with a survival time of between four hours and 2.5 years. This series was compared with a group of 44 neurologically normal controls (age range 51 to 80 years). Immunostaining with an antibody to beta AP confirmed the original findings that 30% of cases of head injury have beta AP deposits in one or more cortical areas. Increasing age seemed to accentuate the extent of beta AP deposition and potential correlations with other pathological changes associated with head injury were also investigated. In addition, beta amyloid precursor protein (beta APP) immunoreactivity was increased in the perikarya of neurons in the vicinity of beta AP deposits. The data from this study support proposals that increased expression of beta APP is part of an acute phase response to neuronal injury in the human brain, that extensive overexpression of beta APP can lead to deposition of beta AP and the initiation of an Alzheimer disease-type process within days, and that head injury may be an important aetiological factor in Alzheimer's disease.